ANALISIS MOTIVASI KERJA, KOMPETENSI, KETERIKATAN KERJA, DAN KINERJA GURU SERTA PEMBINA INSAN CENDEKIA BOARDING SCHOOL (ICBS) HARAU PAYAKUMBUH - Yusriadi Yusriadi; Dika Irawan; Sandi Fadilah (Komunitas Manajemen Kompetitif, 2025)
This study aims to descriptively analyze work motivation, competence, work engagement, and the performance of teachers and supervisors at Insan Cendekia Boarding School (ICBS) Harau Payakumbuh. The study employed a descriptive quantitative approach with a total of 211 respondents. Data were collected using a Likert-scale questionnaire and analyzed through descriptive statistical techniques, including mean scores and class interval categorization. The results indicate that, in general, work motivation, competence, work engagement, and the performance of teachers and supervisors fall into the good category. However, several indicators related to welfare and professional development remain in the fairly good category, particularly those concerning allowances, future security, and the production of scientific publications. These findings provide managerial implications for educational institution administrators in formulating sustainable human resource management policies.